Electronic, Optical and Magnetic Properties of Self-assembled Quantum Dots Containing Magnetic Ions - Trojnar, Anna (Université d'Ottawa / University of Ottawa, 2013)
There is currently interest in developing control over the spin of a single Manganese (Mn) ion, the atomic limit of magnetic memory, in semiconductor quantum dots (QDs). In this work we present theoretical results showing how one can manipulate the spin of Mn ion with light in a QD by engineering Mn-multi-exciton interactions through quantum interference, design of exciton and bi-exciton states and application of the magnetic field. We develop a fully microscopic model of correlated exciton and bi-exciton interacting with the Mn ion. The electrons and heavy holes, confined in the QD, approximated as a two-dimensional harmonic oscillator (HO), interact via direct and short- and long-range exchange Coulomb interactions. The matrix elements of the exchange interaction are computed for the first time in the harmonic oscillator basis and for arbitrary magnetic fields. The exciton and bi-exciton energies and states are computed using the configuration interaction method. The interaction between carriers and the Mn spin is accounted for by the Heisenberg electron-Mn and Ising hole-Mn exchange interactions. For a single exciton confined in a magnetic dot, a novel quantum interference (QI) effect between the electron-hole Coulomb scattering and the scattering by Mn ion is obtained. The QI significantly affects the exciton-Mn coupling, modifying the splitting of the emission/absorption lines from the exciton-Mn complex depending on the degree of electronic correlations in the exciton state. The second signature of the QI are the nonuniform energy gaps between the consecutive emission peaks due to the scattering of carriers by Mn among single-particle orbitals. Magneto-photoluminescence experiments show that the coupling between the exciton and Mn ion does not change in the magnetic field. We report that electron-hole correlations counteract the magnetic squeezing of the single-particle wave functions strengthening the carrier-Mn interactions. As a result, the rate of change of the magneto-photoluminescence spectra with magnetic field is reduced as observed in the experiment. We develop here for the first time a microscopic theory of bi-exciton-Mn complex, and report the presence of the fine structure of bi-exciton-Mn complex, even though as a spin-singlet it is expected to decouple from the localized spin. Theoretical results are compared with experiments in Grenoble and Warsaw.
Keywords: quantum dots; magnetic ion; single spin control